2017
DOI: 10.1074/jbc.m117.811489
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms contribute to increased neutral lipid accumulation in yeast producing recombinant variants of plant diacylglycerol acyltransferase 1

Abstract: The apparent bottleneck in the accumulation of oil during seed development in some oleaginous plant species is the formation of triacylglycerol (TAG) by the acyl-CoA-dependent acylation of -1,2-diacylglycerol catalyzed by diacylglycerol acyltransferase (DGAT, EC 2.3.1.20). Improving DGAT activity using protein engineering could lead to improvements in seed oil yield ( in canola-type ). Directed evolution of DGAT1 (BnaDGAT1) previously revealed that one of the regions where amino acid residue substitutions lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…DGAT1 has been shown to be modulated by its substrate, acyl‐CoA, which binds to an allosteric site at the N‐terminus (Caldo et al, ; Weselake et al, ). The presence of this allosteric site for acyl‐CoA agrees with kinetic studies of microsomal and purified plant DGAT1 showing that DGAT1 exhibits positive cooperativity with acyl‐CoA (Caldo et al, ; Roesler et al, ; Xu et al, ). Interestingly, CoA was identified as a feedback inhibitor of BnaDGAT1 and was shown to bind to the same allosteric site for acyl‐CoA.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…DGAT1 has been shown to be modulated by its substrate, acyl‐CoA, which binds to an allosteric site at the N‐terminus (Caldo et al, ; Weselake et al, ). The presence of this allosteric site for acyl‐CoA agrees with kinetic studies of microsomal and purified plant DGAT1 showing that DGAT1 exhibits positive cooperativity with acyl‐CoA (Caldo et al, ; Roesler et al, ; Xu et al, ). Interestingly, CoA was identified as a feedback inhibitor of BnaDGAT1 and was shown to bind to the same allosteric site for acyl‐CoA.…”
Section: Introductionsupporting
confidence: 81%
“…Many improved BnaDGAT1 variants were generated using the aforementioned method and the two most promising ones were used to increase the oil content of tobacco leaves (Chen et al, ). Kinetic analysis indicated that one of the BnaDGAT1 variants exhibited apparent decreased substrate inhibition at concentrations of acyl‐CoA beyond 5 μM (Xu et al, ). The possible role of the ninth and tenth predicted TMD in enzyme regulation was also identified as a considerable number of beneficial mutations were localized near and within this region (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plots of reaction velocity as a function of increasing oleoyl‐CoA concentration were fitted with the Michaelis–Menten equation or the Hill model. Based on R 2 values, the Hill equation was the preferred model, suggesting that BnaDGAT1 exhibits cooperative substrate binding behavior with oleoyl‐CoA (Table ), as recently described for recombinant BnaDGAT1 in yeast microsomes (Caldo et al ., ; Xu et al ., ). The microsomal preparation, however, is subject to possible interference with other proteins that interact with acyl‐CoA, but the current results obtained with purified protein are similar to that observed using microsomes containing recombinant enzyme.…”
Section: Resultsmentioning
confidence: 97%
“…This result suggests that BnaDGAT1 undergoes substrate inhibition. Once oleoyl‐CoA concentrations greater than 5 μM are reached, the plot prefers a combined model for the Hill equation and substrate inhibition (Table S1), which was recently used to account for the effects of increasing oleoyl‐CoA concentration on the activity of recombinant BnaDGAT1 in yeast microsomes (Xu et al ., ). The combined model was previously proposed for another acyltransferase that exhibited the same kinetic behavior (Dovala et al ., ).…”
Section: Resultsmentioning
confidence: 97%